'Herstories': Using an Historical Lens to Examine Continuities and Changes in Early Childhood Teacher Education. Issue 4 (December 2013) - Whitehead, Kay; Krieg, Susan
THIS ARTICLE SITUATES THE Child Care Act (1972) in a broader account of early childhood education and care, teacher education and the dynamics of inequality over the past century. Our specific focus is the preparation of early childhood educators to work with 'other people's children' (Delpit, 2006) both historically and in contemporary times. We describe Marjorie Hubbe's studies at the Adelaide Kindergarten Training College from 1911–13 before exploring the raft of policy decisions in the 1970s which have led to the current integration of early childhood education and care in Australia. The impact of these changes is highlighted in our discussion of 'Joanne's' preparation to teach other people's children in the twenty-first century.